Financial Ratios and Firm Value: A Reassessment of ROE, CR, and DER: Rasio Keuangan dan Nilai Perusahaan: Penilaian Ulang terhadap ROE, CR, dan DER - Devi Alifatul Khusniah; Nurasik (Academia Open, 2024)
This study reevaluates the consistency of financial ratios, specifically profitability, liquidity, and solvency, in influencing firm value, as measured by Price to Book Value (PBV). Employing a quantitative approach, the research utilizes descriptive statistical analysis, R Square determination, multiple linear regression modeling, and partial t-test hypothesis testing, with data analyzed using IBM SPSS Version 26. The population consists of companies listed in the LQ45 index for the years 2019-2020, and purposive sampling criteria are applied. The results demonstrate that three factors, Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER), exert both simultaneous and partial influences on firm value, shedding light on their significance in the evaluation of company performance.Highlights : This study examines the impact of financial ratios (profitability, liquidity, and solvency) on firm value, measured by Price to Book Value (PBV). It employs quantitative methods, including descriptive statistics, regression analysis, and hypothesis testing using IBM SPSS. The research population comprises companies listed in the LQ45 index for 2019-2020, and the results indicate that Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) have both simultaneous and partial effects on firm value, highlighting their importance in assessing company performance. Keywords: Financial Ratios, Firm Value, Profitability, Liquidity, Solvency